Experiments with a fast String: Searching Algorithm - Møller-Nielsen, Peter; Staunstrup, Jørgen (DAIMI Report Series, 1983)
Consider the problem of finding the first occurrence of a particular pattern in a (long) string of characters. Boyer and Moore found a fast algorithm for doing this. Here we consider how this algorithm behaves when executed on a multiprocessor. It is shown that a simple implementation performs very well. This claim is based on experiments performed on the Multi-Maren multiprocessor.